Entre resistências e inserções: a construção da Agroecologia na Embrapa - Camargo, Vanessa Ortiz de (2009)
The goal of this dissertation is to investigate as agroecology, alternative approach to agriculture characterized by socio-environmental concerns, becomes a prospect that internalises in public institutions of research devoted to agriculture. Analyzing the case of Empresa Brasileira de Pesquisa Agropecuaria (Embrapa), which was historically linked to agricultural modernization in Brazil, the research aims to investigate what the conditions of insertion of the agroecology theme is how the process of legitimation of this. The research consisted of a case study on the institutional process of legitimization of agroecology in EMBRAPA. First, we analyze the official discourse of the company, the institutional position, defined in documents published on the subject. A second step of analysis aims to evaluate how this process is reflected in the level of daily practices of agents. For this, interviews were conducted with experts and researchers from Embrapa Meio Ambiente, located in Jaguariúna- SP. Understanding the Embrapa Meio Ambiente as a field of provisions in dispute, where the agents compete for the accumulation of specific, we show that the environmental issue, and particularly the discussion agroecology, introduce new elements and provide conflicting dynamics. The agroecological perspective takes a marginal seat, or dominated the field in relation to conventional farming, and thus the defenders of agroecology looking agents make use of various strategies, seeking state their views and their understanding of science. If on the one hand social movements seeking intervention in the company entering new perspectives on the other hand, the institution makes use of a series of devices to accommodate new practices to their routines.